Autoevaluación de la práctica docente en estrategias para la evaluación de aprendizajes en estudiantes de las instituciones educativas de nivel primaria I.E.P. Elzeario Mac Donald E I.E.P. N° 60078, Pebas 2021 - Villacorta Ahuanari, Richard (2024)
The research describes the level of self-evaluation of strategies for the evaluation of learning as a teaching practice in students of the Primary Education Institutions I.E.P. Elzeario Mac Donald and I.E.P. N° 60078 in Pebas in 2021, to fulfill it, the descriptive, field, univariate and cross-sectional type was designed, a questionnaire was elaborated to collect data, through a survey. The population and sample were constituted by 101 teachers. The research concludes that the level of self-evaluation of learning evaluation strategies in the students of the 101 (100.0%) teachers is good in 75.2% (76), regular in 16.8% (17) and deficient in 7.9% (8). Likewise, the confirmation of the normality of the data and the hypothesis test based on the student’s t-test support the premise that the level of strategies to evaluate learning in these institutions significantly exceeds the average established in μ = 45 points. These results validate the hypothesis that teachers are applying effective evaluation strategies in the classroom.